"Double-yielding" behavior and progressive β → α → twins transformation in a Ti-based metallic glass matrix composite. (September 2022) - Zhu, R.T.; Yuan, J.L.; Wang, Z.; Shi, X.H.; Yang, H.J.; Qiao, J.W.
Abstract: A Ti-based metallic glass matrix composite (MGMC) exhibits strong work-hardening ability and superb uniform elongation. At 298 K, the yielding strength (YS) reaches 1100 MPa and the uniform elongation (UE) is 7.8%. The rare "double-yielding" phenomenon occurs at room temperature and disappears at cryogenic temperature. At 77 K, the YS reaches 1550 MPa and the UE is 5.3%. Different deformation mechanisms of martensite transformation and α → twins transformation proceed at room and cryogenic temperatures, respectively. It provides guidance for exploring the effect of martensite transformation in MGMCs and developing high-performance MGMCs. Graphical abstract: Image, graphical abstract